El retorno social de la inversión: ¿se puede medir el impacto de la difusión de un proyecto de responsabilidad social empresarial? - Sáenz Acosta, César (2014)
In this document, which is the result of a research project, the influence of attitudinal change and its internal diffusion among the users of a Social Responsibility Project is appraised against the achievement of the purposes of that project. The case study method was used. The target audience consisted of entrepreneurs who participated in a capability development program in a social responsibility project in the telecommunications sector. The results show that 1) the creation of behavioral change, and more specifically, its rapid diffusion among users of the project, have a positive effect in the accomplishment of its objectives, 2) this effect may be estimated by means of Social Return on Investment (sroi), and 3) companies that favor Social Responsibility projects can improve their performance if they bring about behavioral change among their users or beneficiaries